Emerging Trends in Waste Management in the Indian Era - Kadhar Lal, A.; Devamaindhan, B. (Indian Journal of Marketing, 2009)
This study summarizes the findings of a non-lending analytical activity carried out by the World Bank. The work was driven by concern over the quality of the urban environment, undertaken in a context of uncertainity on the suitability and effectiveness of bank investment in this area,particularly in regard to components that generate little or no revenue,like waste disposal and sewage treatment.